Design of an Optimal off-grid Hybrid Energy System for a Rural Community - Borweh, Wemogar Elijah; Frimpong, Emmanuel Asuming; Mensah, Lena Dzifa (JURNAL NASIONAL TEKNIK ELEKTRO, 2018)
This paper presents an optimized off-grid PV-diesel generator-battery hybrid energy system for application in an un-electrified rural community and further outlines a procedure for designing such an economical and technically feasible hybrid system. The hybrid optimization model for multiple energy resources (HOMER) software was utilized for simulation and analysis. The criteria of minimum net present cost of system, low CO2 emissions and zero electric load rejection was applied while considering technical issues of PV array, inverter coordination and PV capacity penetration level. For the case study system used, the obtained optimized hybrid energy system configuration is as follows: 68kW PV plant; 40kW Diesel plant; 45.4kW Inverter; and 80kWh battery unit. The proposed hybrid energy system is capable of producing 157685kWh of electricity annually at a levelized cost of energy of 0.55 $/kWh while emitting 51,000 kg of CO2 yearly. To avoid self-shading of the PV array, an appropriate inter-row distance was determined. The total quantity of PV modules and the electrical configuration of the PV array is presented.  Keywords : Hybrid energy system,  Net present cost,  Optimal sizing and  Photovoltaic